(untitled) (GEON Journal (Management, Organizations and Business), 2024)
Process management is a methodology focused on optimizing processes in companies. Unfortunately, not all owners or managers of organizations know it and much less apply it, generating a lack of continuous improvement of processes, thereby losing the opportunity to increase the competitiveness of the company. Therefore, the objective of this research is to analyze if there is any relationship between the process operation model and an improvement in competitiveness in accounting firms in the city of Puebla, Mexico. To achieve the above, a quantitative investigation was carried out, data collection was obtained by applying a questionnaire to 30 managers or owners of accounting firms located in the city of Puebla, analyzing in a descriptive and correlational manner in the SPSS statistical software. . The main findings of the research show that the offices do not have adequate planning and do not carry out adequate monitoring and control of their operations. Furthermore, they do not use tools that facilitate the evaluation and fulfillment of their organizational objectives, finally reflecting the absence of methodologies. for continuous improvement. The article addresses the discussion of the influence of operating under processes on the competitiveness of accounting firms. In conclusion, it was identified that there is a correlation between the variables analyzed and the need to implement this model in those offices and companies that wish to be more competitive is determined. Likewise, the importance of carrying out subsequent studies with a greater scope in companies in this sector is highlighted. This research is considered original, due to the analysis of process-based management and the influence on competitiveness in the specific context of accounting firms, providing evidence of an understudied field.